The driver in the driverless car: How our technology choices will create the future - Vivek Wadhwa (BK business book., 2017)
Technology is advancing faster than ever--but for better or for worse? On the one hand, astonishing technology developments such as personalized genomics, self-driving cars, drones, and artificial intelligence could make our lives healthier, safer, and easier. On the other hand, these very same technologies could raise the specter of a frightening and alienating future--eugenics, a jobless economy, a complete loss of privacy, and an ever-worsening spiral of economic inequality. How can we make appropriate decisions about whether and how to adopt new technologies? Vivek Wadhwa and Alex Salkever propose that we ask three questions: Does the technology have the potential to benefit everyone equally? What are the risks and the rewards? Does the technology more strongly promote autonomy or independence? They subject a host of new and potential technologies to these questions, but ultimately it is up to the reader to make the final decision. -- Provided by publisher.